Modul Anticipatory Guidance Merubah Pola Asuh Orang Tua yang Otoriter dalam Stimulasi Perkembangan Anak - M. Hasinuddin; Fitriah Fitriah (Jurnal Ners, 2011)
Introduction: Anticipatory guidance is a method used by nurses to help parents provide the development of behavior change towards a better understanding of their children. The purpose of this study was to analyze the provision modul of anticipatory guidance to parents and their effects on patterns of authoritarian parenting in stimulating development in kindergarten Dharmawanita Bangkalan Regency.Methods: The design in this study was experimental pre post test with control group. The population was the parents of students in Dharmawanita Bangkalan kindergarten in 2010. Respondents were 15 people in the treatment group and 15 people in control group who meet the inclusion criteria. Data collected by using a questionnaire. Data then analyzed using Wilcoxon and Mann Whitney test.Result: The result showed that the differences in upbringing the parents before and after the anticipatory guidance given p value of 0.001, whereas in the control group there was no difference with a p value of 0.083. To find out the difference of counselling terms between treatment and control groups were performed by mann whitney test with p-value (0,004) < α (0.05).  Conclusion:  Based on these results we can conclude that modul of anticipatory guidance has an impact on the upbringing of parents in stimulating growth in children in kindergarten Dharmawanita Bangkalan. Research on the effect of anticipatory guidance by the nurse to child development is necessary as a follow up of this research by considering the factors that in fl uence the development of the child itself.